The Effect of Tax Awareness, Service Quality and Fine Sanctions on Individual Taxpayer Compliance at KPP Pratama Jakarta Pancoran: Empirical Study at Pancoran Pratama Tax Service Office - Awaloedin, Dipa Teruna; Pranoto, Agung; Cik, Achmad; Putra, Suadi Sapta; Pradini, Gagih; Karyatun, Subur (CV ODIS, 2024)
This study aims to determine empirical evidence of the effect of tax awareness, service quality, and penalty sanctions on taxpayer compliance. This study used primary data by distributing questionnaires to taxpayers at KPP Pratama Jakarta Pancoran, the research object. The sampling used in this study was simple random sampling. The number of taxpayers sampled in this study was 100 respondents. Multiple linear regression analysis was used in SPSS (Statistical Package for the Social Science) version 25.0 to determine the effect of the independent variable on the dependent variable. The test data used in this study is a test of validity and reliability. To test the hypothesis in this study, researchers used Test T and Test F. This research data shows that tax awareness and penalty sanctions positively and significantly affect individual taxpayer compliance. The service quality variable shows that the results do not affect taxpayer compliance.